Program Safari Dakwah Syeikh Abdul Basith Musfi Dalam Memperkuat Aqidah Masyarakat Kota Semarang - Mochammad Marteen Ilham; Gunawan Gunawan; Fania Mutiara Savitri (Jayapangus Press, 2025)
The Safari Dakwah Program is an Islamic outreach activity conducted by Syeikh Abdul Basith Musfi in collaboration with PPPA Darul-Qur’an, carried out continuously to directly convey religious messages to the community. One of the da’wah movements aimed at spreading the values of the Qur’an is implemented through the Safari Dakwah Roadshow. The purpose of this study is to describe the challenges faced by Syeikh Abdul Basith Musfi in his da’wah activities, and to explain how the Safari Dakwah program strengthens the aqidah (faith) of the people in Semarang City. This research uses a qualitative approach, with data collected through observation and interviews with Syeikh Abdul Basith Musfi. The results of the study show that the main challenges faced by the preacher in conducting da’wah in Semarang come from differences in cultural and linguistic characteristics, particularly in how these differences emotionally affect the community. As an alternative solution, a cultural approach was taken, along with adapting the da’wah efforts to fit local conditions. The Safari Dakwah program is considered an effective strategy for conveying religious messages to the public. The contribution of this research lies in mapping da’wah activities, and emphasizing the importance of applying a cultural approach and understanding the local community’s characteristics to improve the effectiveness of da’wah.